The Statistical Research in Evaluation of Human Resources Performance in Rail Transport - Daneci Patrau, Daniel (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The world economical reality from the last years allows the making evident of some indubitable defining features: the diversification and the renewal of the goods offer, the progresses in the technology area, the globalization occurence, the growth of clients’and society’s exigencies. The analyse of the human resources performance in the railway transport, which is the main goal of this project, aims the identification of the performance indicators of the wage earner on one hand, and on the other hand the presentation of the relations and of correlations between the wage level, the work age, the work conditions and the requirements of the workplaces for the wage earner from the Constanta CFR railway station.